Energy efficient communities: Analysis of urban certification systems - Sosa, María Belén; Correa, Erica; Cantón, María Alicia (Estudios del hábitat, 2022)
Cities have not been planned consid ering the energy they demand; This has led to conservation at the buil-ding scale. But, the energy efficiency of the city does not depend on the sum of bioclimatic buildings; being the planning of the urban form necessary to combine the performance of the buildings with the environment. There are urban certification systems that improve energy efficiency. This work analyzes four systems (BREEAM, LEED®, Green Star, and CASBEE), detects from the set that which in its categories emphasizes the relationship between urban form and energy consumption; and applies it to a set of cases in the study area. Analysis shows that LEED® places greater importance on urban form planning. However, when evaluating the performance between LEED® and the case studies, it is detected that the urban form-energy consumption relationship is not congruent between the certification requirements and the consumption ob-tained.